The preparation of CIGS (Cu(In,Ga)Se2) by a solution route method - Theeranun Siritanon (2018)
Cu(In,Ga)Se2 (CIGS) nanoparticles which are used as a precursor material for a CIGS absorber layer for CIGS-based solar cells were successfully synthesized by a simple solution route. The dispersed metal ions were reduced simultaneously in the solutions using zinc particles. The types of solvent, size of zinc particle, and reaction temperature were studied as the parameters of synthesis. The products were characterized by powder X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), and Energy dispersive X-ray spectroscopy (EDS). It was found that suitable conditions to synthesize CIGS particles were ethylene glycol as a solvent, zinc powder (45 micrometers) as a reducing agent and 60 degree Celsius as a reaction temperature.